HUBUNGAN ANTARA SELF-ESTEEM DENGAN PENYESUAIAN DIRI PADA PASANGAN MUDA DI COFFEE OMAH BEKASI - Arfina Arfina Afriliana; Adi Fahrudin (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
This study aims to find out whether there is a relationship between self-esteem and self-adjustment in young couples in coffee Omah Bekasi. The purpose of this study was to determine the extent of the relationship between self-esteem and self-adjustment in young couples. The research method used is a quantitative research method with a correlational type of research. The sample in this study was 104 respondents. The sampling technique used is nonprobability sampling with sample criteria, namely coffee Omah customers, men and women, aged 20-30 years, and have dating status and marriage. The validity test used is the validity of the contents and the reliability test uses Cronbach- Alpha. The results of the study using statistical analysis of nonparametric correlation Spreaman's rho found that the variability of self-esteem and self-adjustment obtained a significance of 0.000 (p <0.05), which means that there is a positive relationship between the two variables. So, the higher the self-esteem of the individual, the higher the self-adjustment individual. The hypothesis proposed by researchers can be accepted by mentioning the relationship between self-esteem and self-adjustment among young couples.